Term Infant with Cerebral Venous Sinus Thrombosis - Sanket Jani; Ralph Ariss; Pradeep Velumula; Deniz Altinok; Sanjay Chawla (Hindawi Limited, 2020)
Hypernatremic dehydration in neonates is a common condition in an exclusively breastfed infant but often underdiagnosed. Any newborn who has lost more than 10% of birthweight should be carefully evaluated and monitored for clinical features of dehydration. Efforts such as frequent follow-up for weight check, and formula supplementation, if needed, should be provided to a neonate at risk of developing complications of dehydration. Adequate lactation consultation, both inpatient and outpatient, should also be provided, especially to the primigravida mother. Here, we present a case of a neonate with severe hypernatremic dehydration caused by inadequate lactation in a primigravida mother, which resulted in cerebral venous sinus thrombosis leading to significant intracerebral hemorrhage. The infant suffered permanent neurologic damage and was sent home on technological devices (tracheostomy and gastrostomy tubes). Further, we provide a brief review of hypernatremic dehydration and sinus venous thrombosis in neonates.